A STUDY OF FASAKH AND KHULU IN THE COMPILATION OF ISLAMIC LAW (KHI): COMPARISON, CAUSES, AND IMPLICATIONS - Saputra, Deris Arista (Ridwan Institute, 2025)
The Compilation of Islamic Law (KHI), as a legal guideline for Muslims in Indonesia, regulates in detail the Fasakh and Khulu mechanisms in resolving domestic conflicts. This study aims to provide a comprehensive analysis of these divorce mechanisms, focusing not only on their legal aspects but also on their social and psychological implications for individuals and families within the Indonesian Muslim community. The study used a juridical-normative approach that focused on legal analysis contained in the KHI. First, secondary data consisted of books, journals, and articles that discussed this topic from both the perspective of Islamic law and positive law in Indonesia. Then, case studies were conducted by identifying several divorce cases in religious courts. The findings reveal several key points related to the divorce mechanisms in the broader framework of KHI, including a lack of public understanding, social stigma, and limited resources in religious court. Finally, the study provides strategic recommendations for improving their implementation. These findings can inform policymakers, legal practitioners, and community leaders about the importance of these mechanisms in supporting the rights and welfare of individuals within the community.